Evolution and Molecular Epidemiology of Citrus tristeza virus on Crete: Recent Introduction of a Severe Strain. Issue 11 (20th May 2014) - Owen, Carolyn; Mathioudakis, Matthaios; Gazivoda, Anita; Gal, Peter; Nol, Nevena; Kalliampakou, Katerina; Figas, Angela; Bellan, Anais; Iparaguirre, Anais; Rubio, Luis; Livieratos, Ioannis
Abstract Sporadic incidences of Citrus tristeza virus (CTV) in western Crete resulting from the introduction of a mild strain (Spanish isolate T385) have been reported previously. Further analysis within this region has identified an emerging second CTV strain with minimal genetic divergence, sharing 99% nucleotide identity with the severe stem‐pitting isolate Taiwan‐Pum/SP/T1. Other severe isolates from the Mediterranean region appear in the same phylogenetic cluster, indicating movement or new introductions and the need for targeted control actions and improved phytosanitary measures in this area.